Evidence for tocilizumab as a treatment option in refractory uveitis associated with juvenile idiopathic arthritis - Tappeiner, Christoph; Mesquida, Marina; Adán, Alfredo; Anton, Jordi; Ramanan, Athimalaipet V.; Carreno, Ester; Mackensen, Friederike; Kotaniemi, Kaisu; Boer, Joke H. de; Bou, Rosa; Vicuña, Carmen García de; Heiligenhaus, Arnd (The journal of rheumatology, 2016)
Objective. To report on experience using the anti-interleukin 6 receptor antibody tocilizumab (TCZ) to treat severe and therapy-refractory uveitis associated with juvenile idiopathic arthritis (JIA). - Methods. Retrospective data were gathered from patients with JIA receiving TCZ treatment for uveitis. JIA and related uveitis data (disease onset, activity, structural complications, and topical and systemic antiinflammatory treatment) were evaluated at the start of TCZ (baseline) and every 3 months during TCZ therapy. - Results. A total of 17 patients (14 women) with active uveitis were included (mean age 15.3 ± 6.9 yrs, mean followup time 8.5 mos). In all patients, uveitis had been refractory to previous topical and systemic corticosteroids, methotrexate (MTX), and other synthetic and biological disease-modifying antirheumatic drugs, including ≥ 1 tumor necrosis factor-α (TNF-α) inhibitor. Uveitis inactivity was achieved in 10 patients after a mean of 5.7 months of TCZ treatment (in 3 of them, it recurred during followup) and persisted in the remaining 7 patients. By using TCZ, systemic corticosteroids or immunosuppressives could be spared in 7 patients. Macular edema was present in 5 patients at baseline and improved in all of them under TCZ treatment. Arthritis was active in 11 patients at the initial and in 6 at the final followup visit. - Conclusion. TCZ appears to represent a therapeutic option for severe JIA-associated uveitis that has been refractory to MTX and TNF-α inhibitors in selected patients. The present data indicate that inflammatory macular edema responds well to TCZ in patients with JIA-associated uveitis.